EFEKTIVITAS BAKTERI PROBIOTIK DARI UDANG GALAH (Macrobrachium rosenbergii, de Man) TERHADAP BAKTERI PATOGEN Aeromonas hydrophila, Pseudomonas stutzeri DAN Vibrio alginolyticus - Desi Anggreni; Feliatra '; Nursyirwani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractProbiotic bacteria capable of producing substances like antibiotic sandin dispensable for being able to suppressthe growth of pathogenic bacteria into disease and parasites in aquaculture. The research purposeof this study to find probiotic isolates were able to controlthe disease in aquaculture. The candidate probiotic bacteria isolated from prawn (Macrobrachium rosenbergii, de Man) by the method of scratch on TSA and NA media. Anti-bacterial activity using media discs on Zobell and TSA. 4 isolates were found which consisted of coccus, white and orange colonies. All isolates had inhibitory effect onthe growth of pathogenic bacteria. The highest sensitivitytest is indicated by P4 DUG isolates of A.hydrophilla at13,30, 13,20 and14,10 of P.stutzeri in V.alginolyticusKeyword : Probiotic, Effectiveness, Tiger Prawn.